(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Managing the flow of goods and services from point A to point B via a network of intermediaries is the job of supply chain management (SCM). Standard SCM is based on a top-down model, where decisions are made at headquarters and delegated to regional offices. Security, transactional transparency, traceability, stakeholder involvement, product counterfeiting, additional delays, fraud, and instabilities are some of the most pressing issues with current SCM systems. Blockchain (BC) has emerged as a transparent and efficient data management and trust-building tool. It can also help with payments and supply chain transaction authorization and verification without the need for a trusted third party. BC technology is an effective method for fixing current SCM problems. In light of the aforementioned, we present a survey on the use of BC in SCM.This paper reviews the existing research on BC features, applications, and business outcomes across a range of SCM. By reviewing and analysing 97 recent publications emphasising BC’s applications in the supply chain, this Blockchain-centric study reveals the research state and outlines future research directions. Most of the push for BC in SCM comes from its ability to increase trust, transparency, traceability, information sharing, and protection against product counterfeiting. Furthermore, we analysed different SCM applications to determine if and how BC could be used to secure all transactions. The doors are now open for newcomers eager to get to work in this exciting field, as we have highlighted open issues and research challenges for adopting BC technology in SCM.